Barrel-Induced Variation in the Microbiome and Mycobiome of Aged Sour Ale and Imperial Porter Beer. (31st July 2020) - Shayevitz, Avi; Harrison, Keisha; Curtin, Chris D.
Abstract: Traditional styles of beer that undergo spontaneous fermentation and/or maturation in oak barrels are becoming increasingly popular amongst craft beer consumers. These products are costly to produce, partly because some barrels develop undesirable flavor profiles and are excluded from the final blend. As a first step towards understanding variation in beer quality that occurs during barrel maturation, next-generation sequencing was used to profile the bacterial microbiome and fungal mycobiome of three beers; an American Coolship Ale (ACA), an aged sour ale, and an Imperial Porter. For the aged sour ale, produced across three years, it was observed that while there were significant differences in key lactic and acetic acid bacterial genera according to beer age, within each production batch there was substantial barrel-induced variation in microbiome profiles. Similarly, for the Imperial Porter significant differences were observed in the relative abundance of Saccharomyces cerevisiae and Brettanomyces bruxellensis across the barrel population at two sampling time points. Overall, the results point towards barrel-induced variation in the rate of "microbial maturation". Further work to understand the underlying cause of this variation will enable brewers to better predict and monitor their barrel projects to achieve more consistent outcomes.